Artificial Sweeteners: History and New Concepts on Inflammation - Basson, Abigail Raffner; Rodriguez-Palacios, Alexander; Cominelli, Fabio (Frontiers in Nutrition, 2021)
Since the introduction of artificial sweeteners (AS) to the North American market in the 1950s, a growing number of epidemiological and animal studies have suggested that AS may induce changes in gut bacteria and gut wall immune reactivity, which could negatively affect individuals with or susceptible to chronic inflammatory conditions such as inflammatory bowel disease (IBD), a disorder that has been growing exponentially in westernized countries. This review summarizes the history of current FDA-approved AS and their chemical composition, metabolism, and bacterial utilization, and provides a scoping overview of the disease mechanisms associated with the induction or prevention of inflammation in IBD. We provide a general outlook on areas that have been both largely and scarcely studied, emerging concepts using silica, and describe the effects of AS on acute and chronic forms of intestinal inflammation.